(3cJGH aj GdfSH GdTQjas ((3YHOQHg hGUaj YHjd eMehO Hf GdMSjf Hf SGde GdMSfj s)
(3ChdgG (B:s
(3GdMeO ddg GdeJaQO aj GdPGJ hGdUaGJ Qhi GHf YHGS QVj Gddg Yfg Cfg bGd(B: (3deG CQGO Gddg JYGdi Cf jNdb SjO GdChdjf hGdBNQjf bHV bHVI ef GdfhQ Ke bGd dgG chfj MHjHj eMeO s
(3BNQgG (B:s
(3hgPg TLQI ehdGfG ESeGYjd Hf GdTQja Hf Ydj Hf GdMSf Hf eMeO HNW GdEeGe SjOi GdMSf Hf eSYhO GdjhSj Je hced gP GdcJGH s
(3Vef eLehY , JQJjHgG (B: (3ef U (B1 - (3U(B43s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B342 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQHGW (B((3O (B1103) s
Keywords: (3GdJGQjNs